Changes in indigenous population structure in colonial Mexico City and Morelos. (20th February 2019) - Ragsdale, Corey S.; Willermet, Cathy; Edgar, Heather J.H.
Abstract: The Spanish conquest and colonization of Mexico had disastrous effects on indigenous people. Disease, coupled with drastic changes in the economic, political, and religious structures, led to an enormous depopulation event throughout the colony of New Spain. What remains unclear in historic and archeological accounts of Spanish colonization in Mexico is the effects of these changes on indigenous population structure and variation. In this study, we use biological distance and population structure analyses of two Mexico City church ossuary samples from the 16th to 17th centuries, as well as a sample of burials from a convent in nearby Morelos, to investigate these relationships at the center of the Spanish colony in Central Mexico. Colonial samples are compared with a large data set of precontact samples from Central Mexico and the surrounding regions, to evaluate changes in population structures. We compare colonial and precontact samples using biological distance analysis and a population structure program commonly applied in genetic analyses and modified for phenotypic data. Our results show that the colonial Mexico City samples are more biologically similar to the precontact samples from Veracruz, Toluca Valley, and West Mexico than to other precontact samples from the Valley of Mexico. The sample from Yecapixtla in Morelos is also most similar to the Veracruz, Toluca Valley, and West Mexico samples but is also somewhat similar to the precontact sample from Morelos and the nearby Oaxaca Valley. Generally, biological similarities among colonial samples and precontact samples do not correlate with geographic proximity or population size but coincide with cultural changes. Our study provides bioarcheological evidence of some degree of population replacement, resulting either from forced migration from surrounding areas for labor or through indigenous alliances with the Spanish conquerors. Our results also show concordance between traditional biodistance analysis and nontraditional analyses employed in population genetics studies.